(3CMcGe GdfLhes - (3CHh GdYHGS CMeO Hf eMeO Hf YKeGf GdCROi GdeQGcTi , GHf GdHfGAs
(3ChdgG (B:s
(3bGd GdMeO ddg GdYGdi GdbGOQ GdPi Ndb HYO YOe hHYO , aEfg ef JbOe ef GdMceGA fXQhG ai ehLhOGJ NGdbge , aQChgG eMUhQkG hMGUQkG s
(3BNQgG (B:s
(3hGdWGdH GdPci ef hQGA GdHMK hGdfXQ ai cJH gPg GdUfGYI Ef CQGO Pdc , hGddg Gdehab , ced eONd GHf GdHfGA , hddg GdMeO hGdefI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH(B1s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfhGfGJ HGdMeQIs
(3jdjgG aUhd dGHf GdHfGA ai fMh JSY hQbGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B363 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdadcs